Pengaruh Job Satisfaction, Organizational Identification, Job Embeddednes dan Self Effacacy Terhadap Organizational Citizenship Behavior pada Karyawan Perhotelan di Bekasi Barat - Zamzam Nurul Haj; Muhammad Dimas Pangestu; Netania Emilisa (Peneliti.net, 2023)
This article aims to analyze the effect of Job Satisfaction on Organizational Citizenship Behavior on hospitality employees in West Bekasi, to analyze the effect of Organizational Identification on Organizational Citizenship Behavior on hospitality employees in West Bekasi, to analyze the effect of Job Embeddnes on Organizational Citizenship Behavior on hospitality employees in West Bekasi, and to analyze the effect of self-efficacy on organizational citizenship behavior in hospitality employees in West Bekasi. This research is a quantitative research. Collecting data in this study using a questionnaire and literature study. From the results of the study it was found that from the results of the hypothesis testing conducted it was known that the Organizational Identification variable (X_1) had a significance value of 0.002 so that the significance value was less than 0.05, so it could be concluded that H_1 was accepted. The results of the tests that have been carried out show that the Job Satisfaction variable (X_2) has a significance value of 0.000 so that the significance value is less than 0.05, it can be concluded that H_2 is accepted. The results of the tests that have been carried out show that the Job Embeddedness variable (X_3) has a significance value of 0.001 so that the significance value is less than 0.05, so it can be concluded that H_3 is accepted. The results of the tests that have been carried out show that the Self Efficacy variable (X_4) has a significance value of 0.000 so that the significance value is less than 0.05, it can be concluded that H_4 is accepted.